A20 VITAMIN D SUPPLEMENTATION REDUCES THE OCCURRENCE OF COLORECTAL POLYPS IN HIGH-LATITUDE LOCATIONS. (26th February 2020) - Sutherland, R L; Ormsbee, J; Pader, J; Forbes, N; Hilsden, R J; Brenner, D R
Abstract: Background: There is suggestive evidence for the role of vitamin D in the development of colorectal cancer (CRC). Furthermore, previous studies have observed associations with vitamin D supplementation and lower incidence of CRC. Due to high latitudes in Canada, many Canadians are vitamin D deficient throughout winter Aims: In this analysis, we aimed to examine the association between either vitamin D supplement use or meeting the reccommended daily intake of vitamin D, and either any colorectal polyp, or a known precursor of CRC: high-risk adenomatous polyps (HRAPs). Methods: The study population was drawn from the biorepository at the Forzani & MacPhail Colon Cancer Screening Centre (CCSC) in Calgary. Data were obtained from the Diet History Questionnaire (DHQ) I or II, the Health and Lifestyle Questionnaire (HLQ), and through post-colonoscopy reports completed by the endoscopist. Multivariable logistic regression models were used to examine the association between intake of supplemental vitamin D and presence of HRAPs. Models were adjusted for age, sex, BMI, fiber intake, alcohol consumption, and smoking status. Results: Individuals between the age of 50 and 74 years (n= 1, 409) were included. When examining the association between any supplemental vitamin D use and HRAPs, a protective effect was observed with an ORadj of 0.57 (95% CI: 0.33–0.96). Similarly, meeting the recommended daily intake (RDI) of vitamin D (600 IU) was protective against HRAPs with an ORadj of 0.78 (95% CI: 0.62–0.99). Conclusions: This study suggests that adequate vitamin D supplementation can reduce the risk of HRAPs. These results could be used to inform public health recommendations for vitamin D intake with hopes of reducing the risk of HRAPs. Funding Agencies: None